KAJIAN DAMPAK PELAKSANAAN PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) TERHADAP PENDAPATAN USAHATANI PADI DI KECAMATAN LAU KABUPATEN MAROS - Andi Amran Asriadi; Rahmawati Rahmawati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
The research aimed to assess the impact of Gapoktan in implementing agribusiness effort development program and analyzed the activities of agribusiness and development programs in Lau district, Maros Regency. The parameters to be measured are the impact of the development of rural agribusiness of rice farming by farmers.The research used a survey method with interview techniques (questionnaire). Sampling was done by simple random sampling technique by taking as many as 10% of the total respondent in two research villages, where the respondents were selected as many as 52 respondents. The results of the study obtained the level of effectiveness of the results of the study in the implementation of the Rural Agribusiness Development Program on the performance of Gapoktan was quite effective. The performance aspects of the farmer group combination, that was the Interest Level, consisted of Organizational Level with a score of 517 which was quite effective, Fund Management with a score of 517 was quite effective, and Farmer Business with a score of 515 was quite effective. But, the iteam about the Level of Strength consisted of an Organizational Level with a score of 523 being quite effective, Fund Management with a score of 511 was quite effective, and Farming with a score of 511 was quite effective, meaning that the performance program of the farmer group combination members carried out its duties, so the implementation of the above program was quite effective. The rice farming acceptance after the program has increased, the implementation of the program shows a value of -15.778 with a significance of 0.000 < 0.05, Hi accepted means that there is a difference in the level of farmers before and after the significant rural agribusiness development. Program where the average before the program shows farmers' acceptance of Rp. 15,553,192.31, while after the program, the average income of farmers is Rp. 18,791,826.92. Thus, the average difference value was 3,238,634.61 or 20,82%. And, the income from the total cost, so that part of the farmer's income is the value of -14.126 with a significance of 0.000 < 0.05, Hi accepted means that there is a difference in the level of income of farmers in the Rural Agribusiness Development Program. With an average income before obtaining a program fund of Rp. 11,763,124.81 per harvest, while after the program the average income is Rp. 14,681,875.00 per harvest. Thus, the average difference is 2,918,750.19 or 24.81%.